OGG1 and MUTYH repair activities promote telomeric 8-oxoguanine induced senescence in human fibroblasts - Mariarosaria De Rosa; Ryan P. Barnes; Ariana C. Detwiler; Prasanth R. Nyalapatla; Peter Wipf; Patricia L. Opresko (Nature Communications)
Abstract Telomeres are hypersensitive to the formation of the common oxidative lesion 8-oxoguanine (8oxoG), which impacts telomere stability and function. OGG1 and MUTYH glycosylases initiate base excision repair (BER) to remove 8oxoG or prevent mutation. Here, we show OGG1 loss or inhibition, or MUTYH loss, partially rescues telomeric 8oxoG-induced premature senescence and associated proinflammatory responses, while loss of both glycosylases causes a near complete rescue in human fibroblasts. Glycosylase deficiency also suppresses 8oxoG-induced telomere fragility and dysfunction, indicating that downstream single-stranded break (SSB) repair intermediates impair telomere replication. Preventing BER initiation suppresses PARylation and confers resistance to the synergistic effects of PARP inhibitors on 8oxoG-induced senescence. However, OGG1 activity is essential for preserving cell growth after chronic telomeric 8oxoG formation, whereas MUTYH promotes senescence to prevent chromosomal instability from unrepaired damage. Our studies reveal that inefficient completion of 8oxoG BER at telomeres triggers cellular senescence via SSB intermediates which disrupt telomere function.